Severe toxic rhabdomyolysis under combined palbociclib and simvastatin treatment: A case report - Poumeaud, François; Fontanier, Anna; Dion, Jérémie; Mathevet, Quentin; Cointault, Olivier; Uro-Coste, Emmanuelle; Marty, Céline; Dalenc, Florence; Girardie, Pierre; Rataboul, Anaïs (Frontiers in Oncology, 2022)
We report the fourth described case of severe toxic rhabdomyolysis occurring in an 81-year-old woman caused by the concomitant administration of palbociclib taken at the usual dosage (125 mg per day) and simvastatin. To the best of our knowledge, this is the first reported case successfully treated by plasma exchanges, with complete functional recovery within two months. The severity of this case justifies further consideration of pharmacokinetic interactions between palbociclib or other CDK-4-6 inhibitors and statins, which potentially increase the risk of an adverse event.